A comparison between 25 micrograms and 50 micrograms of intravaginal misoprostol for labor induction - Srisomboon J. (2014)
Our purpose was to compare the efficacy 25 micrograms and 50 micrograms dosage of intravaginal misoprostol for labor induction in patients with an unfavorable cervix. Fifty pregnant women were randomly assigned to receive either 25 micrograms (24 cases) or 50 micrograms (26 cases) of intravaginal misoprostol every 6 hours. The mean interval from induction to vaginal delivery was significantly shorter in the 50 micrograms group (13.8 +/- 6.6 hours) when compared with the 25 micrograms group (20.9 +/- 9.5 hours) (P = 004). The average number of misoprostol doses needed per patient was significantly fewer in the 50 micrograms group (1.6 +/- 0.7 versus 2.3 +/- 1.2, P = 0.018). The frequencies of uterine tachysystole were 4.2 per cent and 7.7 per cent in the 25 micrograms and 50 micrograms groups respectively which did not significantly differ. Requirement for oxytocin infusion in the 25 micrograms group was significantly more than in the 50 micrograms group (66.6% versus 23.1% respectively, P = 0.004). Analgesia requirement, delivery method, and perinatal outcomes were comparable in both groups. In summary, intravaginal application of 50 micrograms misoprostol at 6-hour interval is comparable in safety but more effective for labor induction than the 25 micrograms dosage.